Infrared imaging making progress in fulfilling its medical promise. - Head, J.F.
Discusses past, present, and future applications of infrared imaging in medicine. The topics mentioned include: breast cancer; helmet-mounted infrared for battlefield medical application; burns; image analysis and algorithm development.
Keywords: Algorithm development; Battlefield medical application; Breast cancer; Burns; Helmet-mounted infrared; Image analysis; Medical diagnostic imaging